IPv6 PROTOCOL - CHARACTERISTICS AND SUGGESTED METHODS OF IMPLEMENTATION IN EXISTING IPv4 NETWORKS USING CISCO ROUTERS - Kowalik, Piotr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The article constitutes an introduction to IPv6 protocol and is a review of the existing approaches to ensure the coexistence of IPv6 and IPv4, on the example of homogeneous Cisco network infrastructure. In the first paragraph, the IPv6 protocol has been characterized and compared to the IPv4. Then, concepts connected with IPv6 addressing have been described. As the main part, it has been discussed methods to provide the coexistence of the two IP protocols. It has been characterized the primary option which is the dual stack, two types of both point to point and multipoint tunnels and finally - address translation NAT-PT.